Evaluation of the Physicochemical and Techno-functional Properties of Gelatin Extracted from Fish Processing Waste - Joy, Jean Mary; Dara, Pavan Kumar; Amruth, P.; Rosemol Jacob, M.; Dhandapani, Nanjappan; Mathew, Suseela; Anandan, R. (International Journal of Bio-resource and Stress Management, 2023)
The current research was completed at the Indian Council of Agricultural Research - Central Institute of Fisheries Technology (ICAR-CIFT), Cochin, Kerala, India from August 2021 to August 2022 as a modified thermal extraction protocol for deriving gelatin from processing waste of skipjack tuna (Katsuwonus pelamis) skin. The study evaluated the effect of chemical composition and molecular weight contributing to the techno-functional attributes of the resulting gelatin. In the present study, we followed warm water-coupled NaCl pre-treatment to reduce the lipid content of the extracted gelatin. The extracted gelatin was characterized for Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE). The amount of gelatin extracted from the fish skin was 9.30±0.22%. The protein pattern of extracted gelatin on SDS-PAGE was identical to commercial grade gelatin, which implies the purity of extracted gelatin is comparable to that of commercial one. The physicochemical and functional properties were evaluated and pose remarkable techno-functional properties. Therefore, fish processing skin waste of skipjack tuna could be effectively exploited for the preparation of commercial gelatin. The extraction protocol remains environment friendly and this approach remains optimal for food technological applications. The effective exploration contributed to nutritional benefits, technological, functional, and biological functionalities for a large fraction of applications in the area of food technology, nutraceuticals, pharmaceutics, and numerous others as a future line of research.